A COMPANY PROFILE: A WAY TO PROMOTE THE NEW ENGLISH FOR BUSINESS COMMUNICATION PROGRAM OF PETRA CHRISTIAN UNIVERSITY - Jane Gautama; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This Business Communication Final Project (BCFP) is made for English for Business Communication (EBC), a new program of the English Department in Petra Christian University. The background of the study is that only few people know about what EBC is because of EBC’s study focus misunderstanding. Thus, EBC needs a company profile booklet, which functions as not only a resume, but also a marketing tool for EBC, to promote its unique strengths as a new program and attract more potential customers, especially high school students and their parents. The company profile booklet outlines EBC history (“EBC-ED”), general overview (“What is EBC?”), product and service description, successes and milestones (“Why EBC?”), alumni and student testimonials (“What Do Our Alumni and Students Say?), and contact information (“How to Reach Us?”). It is expected that this company profile can benefit EBC in its future growth and development.